A Free-standing Graphene-Polypyrrole Hybrid Paper via Electropolymerization with an Enhanced Areal Capacitance. (10th September 2016) - Shu, Kewei; Wang, Caiyun; Zhao, Chen; Ge, Yu; Wallace, Gordon G.
Abstract: Here we developed a free-standing reduced graphene oxide (rGO)-polypyrrole (PPy) hybrid paper via electropolymerization on a paper-like graphene gel. This flexible hybrid paper displayed a uniform layered structure with PPy coated onto the graphene layers. A high areal mass of 2.7 mg cm −2 could be obtained. It delivered a greatly enhanced areal capacitance of 440 mF cm −2 at 0.5 A g −1, in contrast to that 151∼198.5 mF cm −2 previously reported for graphene paper or polypyrrole-graphene paper. It can retain ∼81% of the initial capacitance at a high current density of 6 A g −1 . The combined high flexibility with outstanding electrochemical performance, makes such novel hybrid paper a promising electrode for flexible supercapacitors.